Recent Advances in Biosensor Technology for Potential Applications – An Overview - Vigneshvar, S.; Sudhakumari, C. C.; Senthilkumaran, Balasubramanian; Prakash, Hridayesh (Frontiers in Bioengineering and Biotechnology, 2016)
Imperative utilization of biosensors has acquired paramount importance in the field of drug discovery, biomedicine, food safety standards, defence, security and environmental monitoring. This has led to the invention of precise and powerful analytical tools using biological sensing element as biosensor. Glucometers utilizing the strategy of electrochemical detection of oxygen or hydrogen peroxide using immobilized glucose oxidase electrode seeded the discovery of biosensors. Recent advances in biological techniques and instrumentation involving fluorescence tag to nanomaterials have increased the sensitive limit of biosensors. Use of aptamers or nucleotides, affibodies, peptide arrays and molecule imprinted polymers provide tools to develop innovative biosensors over classical methods. Integrated approaches provided a better perspective for developing specific and sensitive biosensors with high regenerative potentials. Variety of biosensors ranging from nanomaterials, polymers to microbes have wider potential applications. It is quite important to integrate multifaceted approaches to design biosensors that have the potential for diverse usage. In light of this, this review provides an overview of different types of biosensors being used ranging from electrochemical, fluorescence tagged, nanomaterials, silica or quartz and microbes for various biomedical and environmental applications with future outlook of biosensor technology.